2013
DOI: 10.1088/1674-1137/37/3/038001
|View full text |Cite
|
Sign up to set email alerts
|

A high-pressure study of PbCO3by XRD and Raman spectroscopy

Abstract: A high-pressure study of PbCO 3 by XRD and Raman spectroscopy * ZHANG Yu-Feng( ) 1;2) LIU Jing( ) 1;1) QIN Zhen-Xing(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
5
2
Order By: Relevance
“…It was described earlier that upon compression Pb­[CO 3 ] undergoes two-phase transitions up to 20 GPa, but these do not result in noticeable changes in our Raman spectra (Figure S2). CO 2 -I (dry ice) undergoes a phase transition to CO 2 -III at ≈12 GPa, and the transition may take place in a broad pressure interval. In contrast to earlier studies, our Raman spectra (Figure S2) show the transition at slightly higher pressures (15–20 GPa). This may be due to a pressure gradient in the gasket hole between the position of the ruby and the spot where the Raman data were acquired.…”
contrasting
confidence: 76%
“…It was described earlier that upon compression Pb­[CO 3 ] undergoes two-phase transitions up to 20 GPa, but these do not result in noticeable changes in our Raman spectra (Figure S2). CO 2 -I (dry ice) undergoes a phase transition to CO 2 -III at ≈12 GPa, and the transition may take place in a broad pressure interval. In contrast to earlier studies, our Raman spectra (Figure S2) show the transition at slightly higher pressures (15–20 GPa). This may be due to a pressure gradient in the gasket hole between the position of the ruby and the spot where the Raman data were acquired.…”
contrasting
confidence: 76%
“…As abundant CO 2 -bearing minerals, the thermodynamic properties of carbonates are of particular importance. A significant number of Raman studies of the high-pressure behavior of carbonate minerals have been reported, including aragonite, calcite, vaterite, and other high-pressure CaCO 3 polymorphs (Fong and Nicol 1971;Nicol and Ellenson 1972;Salje and Viswanathan 1976;Liu and Mernagh 1990;Hess et al 1991;Kraft et al 1991;Biellmann and Gillet 1992;Gillet et al 1993;Suito et al 2001;Shi et al 2012;Pippinger et al 2015;Koch-Müller et al 2016;Liu et al 2017;Lobanov et al 2017;Maruyama et al 2017;Bayarjargal et al 2018;Farsang et al 2018;Yuan et al 2019), azurite (Xu et al 2015), cerussite Liu 1997c, 1997b;Minch et al 2010b;Zhang et al 2013;Gao et al 2016), dolomite (Kraft et al 1991;Biellmann and Gillet 1992;Gillet et al 1993; Efthimiopoulos et al 2017Efthimiopoulos et al , 2018Farsang et al 2018;, ikaite…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant carbonates entering the subduction zone are Ca, Mg, and Fe carbonates. At the pressuretemperature (PT) conditions expected for subduction zones and the Earth's mantle, carbonates undergo pressure-and temperature-induced structural changes: CaCO 3 , for instance, undergoes several phase transitions, some of them be-576 N. Biedermann et al: EoS and high-pressure phase behaviour of SrCO 3 coming more relevant to Earth's mantle conditions (Martinez et al, 1996;Santillán and Williams, 2004;Ono et al, 2005a;Oganov et al, 2006;Bayarjargal et al, 2018); other studies have shown the stability and phase transition of dolomite (Zucchini et al, 2017;Solomatova and Asimow, 2017;Efthimiopoulos et al, 2017), which is thought to be the main carbonate phase in subducting slabs. Regarding CaCO 3 , numerous studies on the phase behaviour of aragonite-type CaCO 3 at high pressure reported a phase transition from orthorhombic aragonite (space group Pmcn) into monoclinic CaCO 3 -VII at around 30 GPa and into post-aragonite structure Pmmn at around 40 GPa (Gavryushkin et al, 2017;Bayarjargal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%